Hyaluronic acid–doxorubicin nanoparticles for targeted treatment of colorectal cancer. Issue 1 (28th May 2020) - Pan, Daniel C.; Krishnan, Vinu; Salinas, Alyssa K.; Kim, Jayoung; Sun, Tao; Ravid, Sagi; Peng, Kevin; Wu, Debra; Nurunnabi, Md; Nelson, Jeffery A.; Niziolek, Zachary; Guo, Junling; et al.
Abstract: Colorectal cancer, common in both men and women, occurs when tumors form in the linings of the colon. Common treatments of colorectal cancer include surgery, chemotherapy, and radiation therapy; however, many colorectal cancer treatments often damage healthy tissues and cells, inducing severe side effects. Conventional chemotherapeutic agents such as doxorubicin (Dox) can be potentially used for the treatment of colorectal cancer; however, they suffer from limited targeting and lack of selectivity. Here, we report that doxorubicin complexed to hyaluronic acid (HA) (HA‐Dox) exhibits an unusual behavior of high accumulation in the intestines for at least 24 hr when injected intravenously. Intravenous administrations of HA‐Dox effectively preserved the mucosal epithelial intestinal integrity in a chemical induced colon cancer model in mice. Moreover, treatment with HA‐Dox decreased the expression of intestinal apoptotic and inflammatory markers. The results suggest that HA‐Dox could effectively inhibit the development of colorectal cancer in a safe manner, which potentially be used a promising therapeutic option.